Acute tonsillopharyngitis - a review - Osiejewska, Aleksandra; Gorajek, Anna; Kudan, Małgorzata; Grądzik, Anna; Mikut, Karolina (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Acute pharyngitis and tonsillitis is the most common reason why people want to visit their primary care physician. Viruses are the most common cause of acute pharyngitis and acute tonsillitis in children and adults. The patient complains about pain with sudden onset and throat irritation, pain on swallowing, fever and headache, and in children also abdominal pain, nausea and vomiting. Brief description of the state of knowledge: Most acute tonsillopharyngitis is due to rhinoviruses (35%), influenza (30%), RSV and parainfluenza. Bacteria causes 30% of the infections and S. pyogenes is the most common cause. Viral infections are seasonal. S.pyogenes infection is most often in winter and early spring. Changes in the pharyngeal mucosa look similar in both bacterial and viral etiologies. Because of that, scales have been developed to assess the probability of a bacterial infection. The most used is Centor / McIsaac scale. The gold standard of diagnostics is throat swab culture. In the treatment of streptococcal pharyngitis and tonsillitis, penicillins are used as first-line treatment. Antibiotic treatment reduces infectivity, lowers the risk of rheumatic fever and made symptoms disappear two days earlier. Tonsillectomy does not reduce the number of recurrent pharyngitis and tonsillitis, therefore it cannot be recommended. Conclusion: Acute tonsillopharyngitis can result in many complications, the most serious of them is rheumatic fever. Therefore, it is very important to properly diagnose and use antibiotic therapy when necessary.